PEMBERDAYAAN BERBASIS KOMUNITAS DAUR ULANG SAMPAH DENGAN OPTIMALISASI MEDIA SOSIAL - Eki Afrinaldi; Bukhari; Abdullah Khusairi (JURNAL ILMIAH RESEARCH STUDENT, 2023)
Abstract. This research is motivated by the plastic waste recycling community in marketing the products they have produced, only marketing the products conventionally so that their products are not known to the wider community. Social media as a forum for online sales has not been implemented optimally by them. This type of research is descriptive research which is qualitative in nature. Researchers used a purposive sampling technique. The research results show that the plastic waste recycling community's understanding of social media as a platform for marketing products is limited to their knowledge because they do not really understand digital marketing. The plastic waste recycling community uses social media only for personal or private interests because there are no social media accounts that are managed collectively, only able to use Android as a communication medium, but not yet able to use the applications contained in Android to market products such as Facebook, Instagram, etc. Twitter, Youtube, Tiktok and other social media.